2011
DOI: 10.3736/jcim20110610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taraxerol and taraxeryl acetate on cell cycle and apoptosis of human gastric epithelial cell line AGS

Abstract: Taraxerol has inhibitory effects on AGS cell growth through inducing G(2)/M arrest and promotion of cell apoptosis. Taraxerol acetate has less effect on cell cycle arrest and apoptosis of AGS cells than taraxerol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 4 publications
1
10
0
1
Order By: Relevance
“…The results showed that taraxerol reduced mitochondrial membrane potential dose-dependently. Previous investigations have also indicated that taraxerol prompts apoptosis in human gastric epithelial cells [18]. In the present study, it was observed that treatment of the epithelial cholesteatoma cells with taraxerol caused considerable accumulation of the cells in sub-G1 phase of the cell cycle, resulting in sub-G1 cell cycle arrest.…”
Section: Discussionsupporting
confidence: 62%
“…The results showed that taraxerol reduced mitochondrial membrane potential dose-dependently. Previous investigations have also indicated that taraxerol prompts apoptosis in human gastric epithelial cells [18]. In the present study, it was observed that treatment of the epithelial cholesteatoma cells with taraxerol caused considerable accumulation of the cells in sub-G1 phase of the cell cycle, resulting in sub-G1 cell cycle arrest.…”
Section: Discussionsupporting
confidence: 62%
“…Taraxerol from other plant has already been reported to have plenty of pharmacological activities like antitumor, antiinflammatory, antiproliferative, and antioxidant etc. [ 13 16 ] These reports suggest that C. ternatea may also have potential therapeutic application over skin wound due to the presence of taraxerol. A better separation of the taraxerol marker in the extract was noted by the peak purity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The compound euphol selectively inhibits human gastric cancer cell growth through the induction of ERK1/2‐mediated apoptosis (Lin et al, ). Taraxerol also showed induce G2/M phase arrested and apoptosis in human gastric epithelial cell line (Tan et al, ). In preliminary studies, EA‐induced S‐phase cell cycle arrest led to inhibit cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%